2010
DOI: 10.1016/j.cell.2010.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Chaperonin-Catalyzed Rescue of Kinetically Trapped States in Protein Folding

Abstract: GroEL and GroES form a chaperonin nano-cage for single protein molecules to fold in isolation. The folding properties that render a protein chaperonin dependent are not yet understood. Here, we address this question using a double mutant of the maltose-binding protein DM-MBP as a substrate. Upon spontaneous refolding, DM-MBP populates a kinetically trapped intermediate that is collapsed but structurally disordered. Introducing two long-range disulfide bonds into DM-MBP reduces the entropic folding barrier of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
163
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(183 citation statements)
references
References 45 publications
15
163
1
Order By: Relevance
“…Unlike ribosome bound chaperones (TF, NAC and RAC) and Hsp70, that primarily functions in the de novo folding process by holding newly synthesized chains in a folding competent state, the cylindrical chaperonin complexes are presumed to work like an Anfinsen's cage where the unfolded polypeptide in the central cavity of chaperonin is secluded from the cellular milieu. Under these conditions, similar to infinite dilution, the unfolded polypeptide achieves its native state according to its thermodynamic potential (Ellis, 1994 (Chakraborty et al, 2010).…”
Section: Ii4113 the Chaperoninsmentioning
confidence: 99%
“…Unlike ribosome bound chaperones (TF, NAC and RAC) and Hsp70, that primarily functions in the de novo folding process by holding newly synthesized chains in a folding competent state, the cylindrical chaperonin complexes are presumed to work like an Anfinsen's cage where the unfolded polypeptide in the central cavity of chaperonin is secluded from the cellular milieu. Under these conditions, similar to infinite dilution, the unfolded polypeptide achieves its native state according to its thermodynamic potential (Ellis, 1994 (Chakraborty et al, 2010).…”
Section: Ii4113 the Chaperoninsmentioning
confidence: 99%
“…However, for all practical purposes, this temporal cross-talk is negligible and is typically less than 1 %. Differences in donor and acceptor quantum yields, f D,A and detection efficiencies were accounted for by g [Equation (6)]. …”
Section: Calculation Of Fret Efficiency and Stoichiometrymentioning
confidence: 99%
“…Ha and coworkers showed that it is possible to perform FRET investigations with single-molecule sensitivity, [4] which has led to the wide spread use of single-pair FRET (spFRET) to investigate intra-and intermolecular distances and thereby conformations and dynamics in order to provide new insights into a number of biological questions. [5][6][7][8][9][10][11][12][13][14][15][16][17] SpFRET measurements can be performed either on immobilized molecules or on molecules in solution using a burst analysis. [18] In the solution-based experiments, the fluorescence of a dilute (of the order of 20-50 pm) solution of labeled molecules coming from the~fL volume of the focus of a confocal microscope is measured using a high numerical aperture objective.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, important aspects of chaperonin function were reported by Tang et al (6) and Chakraborty et al (8). Using SR variants of GroEL, they extensively studied chaperonin-mediated folding of maltose binding protein, especially its mutant with two amino acid replacements (DMMBP; V8G/Y283D).…”
mentioning
confidence: 99%
“…The passive Anfinsen cage model explains that proteins fold in a spontaneous manner in the cage without the risk for aggregation (4). The confinement model proposes that proteins folding in the narrow space of the cage destabilize off-pathway (or slow) folding intermediates and can be more rapid than the spontaneous folding (5)(6)(7)(8). These models assume that a substrate protein starts folding essentially as a free polypeptide in the cage on GroES binding.…”
mentioning
confidence: 99%